Enhancing School Management Efficiency through Digital Classroom Management: A Comparative Study of Kenya and Indonesia - Mohamed, Alwy Ahmed; Anggraini, Fadhilla Nangroe; Shohib, Muhammad Wildan; Harun, Hannan Zakirah; Alaa Alkhateeb, Alaa Alkhateeb (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
This study investigates and compares digital classroom management practices in Kenya and Indonesia, with particular attention to the extent to which digital tools contribute to the efficiency of school management and instructional processes. Using a cross-national comparative design, a systematic survey was administered to 200 participants, comprising teachers and students from elementary, junior high, and senior high schools, in both countries. The data were analysed using descriptive statistics, independent-samples t-tests, and regression analyses to examine differences between contexts and to assess the relationship between digital classroom management practices and learning-related outcomes. The findings indicate that digital classroom management has been adopted in both Kenya and Indonesia; however, significant disparities persist in terms of technological infrastructure, teacher digital competence, and access to learning resources. Indonesian schools demonstrate a higher level of integration with digital platforms, whereas Kenyan schools exhibit greater adaptability and innovative use of limited resources. Regression results further reveal that infrastructural readiness, teacher competency, and student engagement are significant predictors of effective digital classroom management. These comparative insights contribute to the literature on digital school management by highlighting contextual factors shaping digital implementation in developing countries. The study offers evidence-based policy and practice recommendations to support more equitable and effective digital classroom management across diverse educational settings.